The New Role of the Nonprofit Sector - Albassam, Bassam Abdullah (Mediterranean Journal of Social Sciences, 2012)
For decades, serving the public has been the main function of nonprofit organizations. They have also been involved inother functions such as participation in the policy process, but not so significantly as to have influence in policy-making andimplementation. In recent years, however, the role nonprofit organizations play in the national economy and political process hasincreased. In addition, the relationships between the nonprofit (independent) sector and the public and private sectors havechanged, causing politicians and scholars to rethink the nonprofit sector’s increased influence on the local and national economyand policy process. This paper explore the new role that the nonprofit sector has begun to play in shaping and influencing thelocal and national economy and policy process in the United States in the last few decades. The paper concludes thatlegislations and rules that deal with the way nonprofit organizations participate in the policy process need to be updated toconsider the increasing role of the sector.